ANALISIS ION Cd(II) MENGGUNAKAN RESIN TERMODIFIKASI ABU KULIT SINGKONG - Ca - ALGINAT SEBAGAI BAHAN PENGISI KOLOM DALAM TAHAPAN PRAKONSENTRASI - Rientha Septiana; Aman Sentosa Panggabean; Bohari Yusuf (PROSIDING SEMINAR KIMIA, 2017)
Ca-Alginate (CAA) resins modified by ash of cassava roots bark (ACRB) and utilized as material for column filler in ion preconcentration stage has been carried out. Preconcentration method was carried out by off-line method, sample poured into column by down flow, eluted by 1,0 M HCl and measured by Atomic Absobtion Spectrofotometer (AAS). Optimum component to produce modified microcapsule ACRB-CAA in mixture of 1% Na-Alginate, 1M CaCl2 and 0,05 gr of ACRB. The result revealed that ion Cd(II) retention in pH 4, sample volume and eluent HCl were 10 mL and 4 mL respectively and retention capacity 1,3705 mg Cd/gr resins. This method achieved a good result for Cd ion analysis with limit of detection 0,0101 mg/L and 1,29% of %CV and can be applied for ion Cd analysis of sample water from environment with percent of recovery >95% by spike method. Environmental sample taken from Mahakam River, well-water, ex coal excavation site. Keywords : Preconcentration, Modified resins Ash of Cassava Roots bark - Ca - Alginate